Modeling the electric degradation of podocytes and detection of albumin for the early diagnostics of the glomerulus's damage - Nieto Chaupis, Huber (2017)
In this paper, the pass of proteins like the albumin through the glomerular layers is modeled. Mainly, we have focused on the mathematical model based on physics which might explain the filtering of giant proteins like the albumin to the convoluted tubule as a relevant indicator of the beginning of the diabetes kidney disease (DKD). The main assumption of this study is that of the presence of high concentrations of glucose might deplete the negative charges (superficial densities) located along the endothelium and podocytes. This has implications on the podocytes's architecture in the sense that the lack of charges is synonymous of degradation and loss of functionalities. When podocytes have lost their morphology, the albumin and others negatively charged proteins exert electrical forces on the slit diaphragm and therefore makes a dynamical displacement in the Bowman's space or urine formation space. We have simulated the possible spatial configurations of albumin and noise expected to be measured by the nanosensor. The results are interpreted as the possible beginning of the glomerular damage in type-2 diabetes patients. The Monte Carlo simulation yields that the signal can be measured with an efficiency of order of 70%.